Remineralization and inactivation of carious lesions treated with silver fluoride in Brazilian children with special healthcare needs - Potgieter, Nicoline; Pereira, Viviane; Elias, Roberto; Charone, Senda; Groisman, Sonia (Frontiers in Oral Health, 2024)
Introduction Providing conventional, restorative dental care to children with special healthcare needs (CSHCN) often requires sedation using general anesthesia. Saliva consistency, diet, and oral hygiene practice are different for CSHCN, and limited evidence is available on the efficacy of silver fluoride (SF) for the management of carious lesions for this vulnerable population. Methods Parents of CSHCN were educated about silver fluoride as a treatment option for caries. In total, 550 carious lesions from 100 participants were identified and scored according to the Nyvad Caries criteria. A total of 100 lesions with Nyvad scores 1, 2, and 3 were treated with a single application of silver fluoride and observed postoperatively at 1, 3, and 6 weeks. Result The results indicate statistically significant (p < 0.05) differences in lesion remineralization over the 6-week follow-up period. At the 6-week follow-up, more than 85% of all lesions were remineralized across all children, regardless of condition or original Nyvad score of 1, 2, or 3. Conclusion A single application of silver fluoride has demonstrated effectiveness in remineralization and inactivation of carious lesions over 6 weeks among Brazilian CSHCN. Silver fluoride should be considered an option for the management of carious lesions among CSHCN. Further studies are recommended, including larger sample sizes, longer follow-up times, a second application of SF, and different special needs conditions.